Skrining Isolat Bakteri Asam Laktat Penghasil Bakteriosin yang Diisolasi dari Asinan Rebung Bambu Tabah dan Ketahanannya terhadap Panas - Sujana, I Gede Arya; Antara, Nyoman Semadi; Gunam, Ida Bagus Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): DesemberDO - 10.24843/JRMA.2020.v08.i04.p15, 2020)
The aim of this study to determine the Lactic Acid Bacteria (LAB) isolated from pickled tabah bamboo shoots can produce bacteriocins and the resistance to heat. This research was conducted in two stages, namely: 1) Screening of LAB isolates producing bacteriocin and 2) Testing the effect of heating temperatures of 80°C, 100°C and 121°C for 5, 10 and 15 minutes and without heating to bacteriocin resistance activity. In this study, the screening stage was carried out in two stages, namely: 1) antibacterial test with cell free supernatant and 2) antibacterial test with neutralized cell free supernatant. The resulting clear zone is observed then followed by calculating the value of Arbitrary Units (AU). The bacteria used as an indicator is Lactobacillus plantarum which is Gram positive bacteria. The results of this study indicated that of 88 LAB isolates there were 27 isolates that were able to produce bacteriocin. From 27 isolates, there were three isolates with the most potential to produce bacteriocins, namely isolate PR.6.10.5 with an inhibition zone of 17.67 mm and a bacteriocin activity value of 264.81 mm 2 /ml, isolate PR.6.15.2 with an inhibition zone of 17.33 mm and the bacteriocin activity value of 259.57 mm 2 /ml and isolate PR.3.15.1 with an inhibition zone of 17.00 mm and a bacteriocin activity value of 254.34 mm 2 /ml. Bacteriocins from LAB isolates isolated from pickled tabah bamboo shoots were able to withstand heating to a temperature of 121°C for 15 minutes. Bacteriocin activity decreased by an average of 27.75% after heating at 80°C, 100°C and 121°C for 5,10 and 15 minutes with a bacteriocin activity value from 141.82 mm 2 /ml to 254.34 mm 2 /ml. The smallest decrease in activity value occurred in PR.6.10.5 isolates with an average decrease of 22.98%. Keywords: Screening, lactic acid bacteria (LAB), bacteriocin, heat.